Simulasi Pembangkit Listrik Tenaga Surya Sistem Hybrid PLN PLTS Pada Gedung A Unbari Jambi (Menggunakan Software System Advisor Model (Sam) 2021,12,2) - Suprianto, Agus; Suprapto, Eko; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2025)
Solar panels can be developed to meet the needs of electrical energy. This study was made as a comparison between the costs incurred by Batanghari University when using electricity sources from PLN compared to using electricity sources from solar power plants that are planned, in order to find out the amount of investment costs that are more efficient in a period of months or even years. The design of the calculation of electrical power using SAM, in building A UNBARI. This object was chosen because it uses various electrical loads that are used throughout the day. Load data and total power and electrical energy costs in this building will be used as a comparison for the costs incurred by the planned Hybrid Power Plant (PLTH). The simulation of solar power plants with software with SAM shows that it can almost meet the needs in Building A of Batanghari University and the payback time does not exceed the economic life of a plant, which is 25 years. Based on the results of the study, the PLN PLTS hybrid system project in building A of Batanghari University can be reliably because it meets the eligibility criteria. With data from the results of the calculation of software with SAM, namely a pay back period of 16 years and 4 months, compared to the estimated average lifespan of solar panels which reaches 25 years, the study of PLN PLTS hybrid solar power plants will generate good income for the future.